Defending organized crime? A note - Jürgen G. Backhaus (Universität Konstanz, Fachbereich Wirtschaftswissenschaft und Statistik, 1979)
The objective of this note.is to discuss optimal enforcement strategies vis-a-vis organized and unorganized crime. Taking an earlier contribution by Buchanan as a starting point of the analysis, it is argued that his proposal to monopolize crime in order to reduce the general level of criminal activity is a questionable strategy to curb crime. Syndicated crime is likely to benefit from economies of scale in the provision of non-governmental enforcement of agreements and contracts. The consequent reduction in costs is likely to increase the general level of criminal activity. Nevertheless, the price-theoretic argument is seen as an interesting starting point for the design of new strategies to combat crime.
Keywords: 330